The effect of storage at -20°C and -80°C on HbA1c measurements in whole blood samples analysed using Bio-Rad D-10 - T. Ibrahim, T. Zaharah; Samsudin, Intan Nureslyna; Nasuruddin, Alia Nasriana; Thambiah, Subashini C. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Glycated haemoglobin (HbA1c) is a test commonly measured in many clinical laboratories to monitor and diagnose diabetes mellitus (DM). The laboratory in Hospital Tengku Ampuan Afzan (HTAA) receives HbA1c samples internally and from several other hospitals and clinics in the state of Pahang, at which, before transportation and analysis, the samples are often stored. This study determined the stability of HbA1c samples following different storage temperatures and duration for up to 30 days. Method: Whole blood samples for HbA1c analysis were col- lected from 222 healthy blood donors and type 2 DM (T2DM) patients. Each sample was prepared into four aliquots, which were then stored at temperatures -20°C and -80°C. HbA1c analyses were performed at baseline, days 15 and 30 using ion-exchange high-performance liquid chromatography (HPLC) assay technique on Bio-Rad D-10 analy- ser. HbA1c levels following sample storage were compared to the levels at baseline. Results: The baseline HbA1c (mean±SD) was 6.6±2.2%. At -20°C of storage, the HbA1c levels decreased with a mean difference of 0.1% and 0.3% on days 15 and 30, respectively. Storage at -80°C resulted in a mean difference of 0.1% on day 15 whilst no change was noted on day 30. The number of samples that showed clinically significant HbA1c change (defined as a change of >0.5%) was less for the samples stored at -80°C (4.5%) as compared to -20°C (23%). Conclusion: HbA1c concentration is affected by temperature and duration of sample storage. In instances where prolonged storage of HbA1c samples is expected, storage at -80°C is preferable.